Peningkatan Keterampilan Menulis Teks Laporan Observasi Menggunakan Model Pembelajaran Konstruktivisme - Abdul Rahman; Hajrah; Evi Susianti (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to improve observation report writing skills through the application of the constructivism learning model in Class XII Merdeka 6 SMA Negeri 8 Makassar. The research method used is Classroom Action Research with two cycles. Each cycle consists of planning, implementation, observation, and reflection. The research subjects were students of class XII Merdeka 6 totaling 31 people. Data were collected through written tests of report writing, observation, reflection and analyzed descriptively qualitative. The results showed that the application of the Contructivism Learning model could significantly improve students' report text writing skills. In cycle I, the report text writing skills were still in the sufficient category with a percentage of classical completeness of 67.56%. However, in cycle II, there was a significant increase, with the percentage of classical completeness reaching 91.89%. In addition, observation of learners' participation also showed a significant increase from cycle I to cycle II. The results of this study indicate that the constructivism learning model is effective in improving the skill of writing observation report text.